Prevalence of Menstrual Disorders Related to Body Mass Index (BMI) - Ummah, Wiqodatul; Utami, Woro Tri (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Menstrual problems affect as high as 90% of adolescent females and are the main reason for gynecology visits. Menstruation is a normal physiological phenomenon for females indicating her capability for procreation. Menstrual problems are common in adolescent girls, which may affect their life and outdoor activities. Adolescent girls with abnormal body mass index (BMI) suffer even more often. This study aimed to To assess the relationship between Menstrual Cycle Disorders and Symptoms Menstrual Cycle with BMI among adolescent school in MTs Bustanul Ulum. This study was a cross-sectional study conducted among 30 adolescent school girls of MTs Bustanul Ulum. Permission was obtained from principal of the school and written informed consent was taken from the parents of the school girls before taking part in the study. MC disorders included amenorrhoea, polymenorrhea, oligomenorrhoea, hypermenorrhoea and hypomenorrhoea. MC-related symptoms included dysmenorrhoea and premenstrual syndrome (PMS). All the data were collected, entered, and analyzed in SPSS 17.0. The data were analyzed using percentages and proportions through tables. Out of 30 adolescent girls, 19 (63.3%) were having a BMI 18.5, which implies that 50% of the girls were undernourished. Only 2 (6.7%) of adolescent girls were overweight. Adolescent girls who have a BMI 18.5 experience more symptoms and problems associated with menstrual cycles. This difference was statistically significant. Menstrual problems especially dysmenorrhea are frequent among adolescent girls. BMI play a very vital role for menstrual cycle regularity. Consequently, adolescent girls have to be given healthy and balance nutrition, which leads to maintenance of their normal BMI and regulate their menstrual cycle.